PENGUKURAN KINERJA DENGAN MENGGUNAKAN KONSEP VALUE FOR MONEY PADA PEMERINTAH KAB. OKI SUMATERA SELATAN PERIODE 2017-2019 - Djenni Sasmita (Universitas Muhammadiyah Tangerang, 2020)
This study aims to determine the performance of the Regional Wealth and Financial Revenue Service (DPKAD) of Oki District, South Sumatra by using the concept of Value For Money. This research was conducted by collecting data for 3 years, from 2017 to 2019. This study used secondary data. The data analysis method used is descriptive qualitative analysis method. Based on the results of research using the concept of Value For Money based on 3 main elements, namely economy, efficiency and effectiveness, it shows that: Economic ratios get 86.54%, 82.64% and 71.43%, which means that the economic ratio is below 100% during 2017 -2019 and the results of this ratio indicate that the criteria for economic ratios are categorized as